Signs of meaning in the universe - Hoffmeyer, Jesper (Advances in semiotics., 1996)
For three and a half billion years the living creatures of the natural world have been engaged in an increasingly complex and extensive conversation. Cells, tissue, organs, plants, animals, entire populations and ecosystems buzz with communication, incessantly emitting and receiving signals. These signs have been there as long as life itself. They make up the semiosphere, a sphere like the biosphere, but one constituted of messages - sounds, odors, movements, colors, electrical fields, chemical signals - the signs of life. This book examines the radical premise that the sign, not the molecule, is the crucial, underlying factor in the study of life.